Rechtvacuum in protection for notaries in carrying out their duties in Batam City - Sumarno, Sumarno (Jurnal Konstatering, 2024)
Notaries have an important function as public officials, this is because notaries are needed to make authentic deeds for the purposes of proving the recognition of civil ownership rights to an object. The important position of Notaries is not in line with the existence of clear legal protection for Notaries in carrying out their duties and responsibilities as public officials. The type of research in this thesis is sociological or empirical legal research which includes legal identification and legal effectiveness. Empirical legal research is legal research in which data is obtained through primary legal data or data obtained directly in society. Based on existing studies, it can be concluded that the implementation of protection for Notaries when carrying out their duties in Batam City has not yet been realized because there is no clear mechanism regarding protection for Notaries when carrying out their duties and responsibilities.